Enhancing scholarly use of digital libraries: A comparative survey and review of bibliographic metadata ontologies - Jett, Jacob; Nurmikko-Fuller, Terhi; Cole, Timothy W.; Page, Kevin R.; Downie, J. Stephen (JCDL '16 : proceedings of the 16th ACM/IEEE-CS Joint Conference on Digital Libraries : June 19-23, 2016, Newark, NJ, USA, 2016)
The HathiTrust Research Center (HTRC) is engaged in the development of tools that will give scholars the ability to analyze the HathiTrust digital library's 14 million volume corpus. A cornerstone of the HTRC's digital infrastructure is the workset - a kind of scholar-built research collection intended for use with the HTRC's analytics platform. Because more than 66% of the digital corpus is subject to copyright restrictions, scholarly users remain dependent upon the descriptive accounts provided by traditional metadata records in order to identify and gather together bibliographic resources for analysis. This paper compares the MADSRDF/MODSRDF, Bibframe, schema.org, BIBO, and FaBiO ontologies by assessing their suitability for employment by the HTRC to meet scholars' needs. These include distinguishing among multiple versions of the same work; representing the complex historical and physical relationships among those versions; and identifying and providing access to finer grained bibliographic entities, e.g., poems, chapters, sections, and even smaller segments of content.